Psychological and Pedagogical Bases for Determining the Future of Vocational Education: Vectors of Development - Yu. P. Zinchenko; E. M. Dorozhkin; E. F. Zeer (Russian State Vocational Pedagogical University, 2020)
Introduction. Today, the field of education around the world is facing a protracted crisis caused by the transition to post-industrial society. The dynamic knowledge obsolescence due to the rapid development of science and high technology caused deep structural changes in employment and significantly shortened the life cycle of professions. Modern economy needs specialists with qualitatively new characteristics: a competent and flexible person with meta-professional competencies, who is capable to implement innovative activity and to work in multitasking regime in the situation of instability and uncertainty, and who is ready for active professional self-determination throughout life. Therefore, a radical reorganisation of vocational education system is necessary to be undertaken. It is significantly important to solve this problem through the conduction of professional and pedagogical training of teachers, since the level of their competency primarily depends on the qualitative characteristics of future employees for diverse sectors of the economy and production.The aim of the present article is to define strategic guidelines for predicting the development of professional education in the conditions of post-industrial society.Methodology and research methods. The theoretical and methodological framework of the research is based on the theory of vocational development, the concept of determining the immediate and long-term perspectives of educational sphere, as well as logical-evolutionary, system-dynamic, project-based, personal and convergent approaches. In the course of the research, the methods of analysis, synthesis, generalisation and hypothetical-inductive method were applied.Results and scientific novelty. The trends and directions of vocational education development are identified and described. The principal defining factor of vocational education is close integration of all its processes and subsystems (prevocational, primary vocational, vocational higher secondary and postgraduate education), which integrity is ensured by the continuity and compliance with the principle of advanced education. The concept of convergence and transprofessional in multi-disciplinary training of professionals is revealed. The process of convergence, determining interdisciplinary and prevocational links, ensures transprofessionalism formation - human readiness and participation in the development and realisation of new types of socio-professional activities. A logical and semantic model of a modern specialist is constructed. This model can serve as an empirical basis for designing and supporting a vocational educational platform, which integrates natural science, industrial-technological and socio-humanitarian disciplines and related innovative technologies when training teachers for the system of vocational education. Transprofessionalism, cooperation, collaboration, advanced and high-speed education are highlighted as the vocational training strategies in the conditions of digital transformation of the economy.Practical significance. The research materials can be useful for the specialists in the field of vocational education, for the managerial staff of educational organisations when developing management decisions and organising efficient preparation of teaching personnel.